2019
DOI: 10.1038/s41422-019-0163-6
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical activation of compartmentalized pools of AMPK depends on severity of nutrient or energy stress

Abstract: Wang 18 19 AMPK, a master regulator of metabolic homeostasis, is activated by both 20 AMP-dependent and AMP-independent mechanisms. We investigated the 21 conditions under which these different mechanisms operate, and their biological 22 2 implications. We show that, depending on the degree of elevation of cellular 23 AMP, distinct compartmentalized pools of AMPK are activated, phosphorylating 24 different sets of targets. Low glucose activates AMPK exclusively through the 25 AMP-independent, AXIN-based pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
157
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(167 citation statements)
references
References 77 publications
10
157
0
Order By: Relevance
“…This effect could be mediated by direct activation of AMPK within the α-cell as pharmacological and genetic activation of α-cell AMPK stimulates glucagon secretion (7,8). Importantly, this indicates that the likely net effect of AMPK activation throughout the whole body is to increase glucose delivery to the brain, as previously suggested (22), indicating that at the level of the whole organism, central AMPK activation may supersede peripheral activation in a hierarchical manner, akin to that suggested for subcellular pools of AMPK (26).…”
Section: Resultssupporting
confidence: 64%
“…This effect could be mediated by direct activation of AMPK within the α-cell as pharmacological and genetic activation of α-cell AMPK stimulates glucagon secretion (7,8). Importantly, this indicates that the likely net effect of AMPK activation throughout the whole body is to increase glucose delivery to the brain, as previously suggested (22), indicating that at the level of the whole organism, central AMPK activation may supersede peripheral activation in a hierarchical manner, akin to that suggested for subcellular pools of AMPK (26).…”
Section: Resultssupporting
confidence: 64%
“…Recently, it was demonstrated that different intensities of AMPK stimulation trigger activation of specific subcellular pools, resulting in phosphorylation of distinct downstream targets. Under conditions of glucose starvation that do not elevate cellular adenosine monophosphate: ADP or adenosine diphosphate:ATP ratios, only lysosomal AMPK is activated and exclusively through the lysosomal pathway …”
Section: Resultsmentioning
confidence: 99%
“…Palmitate interacts with CD36 and can palmitoylate it (Tao et al, 1996;Thorne et al, 2010;Zhao et al, 2018). This increases CD36 translocation to the plasma membrane and favors the formation of a complex with Fyn, Lyn and LKB1, preventing AMPK activation under chronic palmitate treatment conditions (Li et al, 2019;Zhao et al, 2018). Acute binding to palmitate, on the other hand, may alleviate LKB1 inhibition, activating AMPK and lipophagy (Li et al, 2019;Samovski and Abumrad, 2019;Samovski et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…This increases CD36 translocation to the plasma membrane and favors the formation of a complex with Fyn, Lyn and LKB1, preventing AMPK activation under chronic palmitate treatment conditions (Li et al, 2019;Zhao et al, 2018). Acute binding to palmitate, on the other hand, may alleviate LKB1 inhibition, activating AMPK and lipophagy (Li et al, 2019;Samovski and Abumrad, 2019;Samovski et al, 2015). Zhang and co-workers elegantly described the mild and early activation of AMPK upon glucose starvation before any changes in ATP levels, in a manner regulated by aldolase activity (a glycolytic enzyme).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation